The role of lysosomal enzymes in killing of mammalian cells by the lysosomotropic detergent N-dodecylimidazole (The Rockefeller University Press, 1987)
The sensitivity of cultured human and hamster fibroblast cells to killing by the lysosomotropic detergent N-dodecylimidazole (C12-Im) was investigated as a function of cellular levels of general lysosomal hydrolase activity, and specifically of cysteine cathepsin activity. Fibroblasts from patients with mucolipidosis II (I-cell disease) lack mannose-6-phosphate-containing proteins, and therefore possess only 10- 15% of the normal level of most lysosomal hydrolases. I-cell fibroblasts are about one-half as sensitive to killing by C12-Im as are normal human fibroblasts. Overall lysosomal enzyme levels of CHO cells were experimentally manipulated in several ways without affecting cell viability: Growth in the presence of 10 mM ammonium chloride resulted in a gradual decrease in lysosomal enzyme content to 10-20% of control values within 3 d. Subsequent removal of ammonium chloride from the growth medium resulted in an increase in lysosomal enzymes, to approximately 125% of control values within 24 h. Treatment with 80 mM sucrose caused extensive vacuolization within 2 h; lysosomal enzyme levels remained at control levels for at least 6 h, but increased 15- fold after 24 h of treatment. Treatment with concanavalin A (50 micrograms/ml) also caused rapid (within 2 h) vacuolation with a sevenfold rise in lysosomal enzyme levels occurring only after 24 h. The sensitivity of these experimentally manipulated cells to killing by C12-Im always paralleled the measured intracellular lysosomal enzyme levels: lower levels were associated with decreased sensitivity while higher levels were associated with increased sensitivity, regardless of the degree of vacuolization of the cells. The cytotoxicity of the cysteine proteases (chiefly cathepsin L in our cells) was tested by inactivating them with the irreversible inhibitor E-64 (100 micrograms/ml). Cell viability, protein levels, and other lysosomal enzymes were unaffected, but cysteine cathepsin activity was reduced to less than 20% of control values. E-64-treated cells were almost completely resistant to C12-Im treatment, although lysosomal disruption appeared normal by fluorescent visualization of Lucifer Yellow CH- loaded cells. It is concluded that cysteine cathepsins are the major or sole cytotoxic agents released from lysosomes by C12-Im. These observations also confirm the previous conclusions that C12-Im kills cells as a consequence of lysosomal disruption.